Whalesuckers and a spinner dolphin bonded for weeks: does host fidelity pay off? - Silva-Jr, José Martins; Sazima, Ivan (Biota Neotropica, 2003)
The whalesucker Remora australis (Echeneidae) is an oceanic diskfish found attached to cetaceans only and its habits are therefore poorly known. At the Fernando de Noronha Archipelago, off North-eastern Brazil, spinner dolphins Stenella longirostris (Delphinidae) regularly congregate in large groups in a shallow bay, which allows for underwater observations of their behaviour and their fish associates. In the course of a broader study of this elusive diskfish, we had the opportunity to made multiple records of two whalesucker couples (three of the fish naturally marked) attached to the same individual dolphin in two different years, over periods of 47 and 87 days respectively. In all the sightings the whalesucker individuals of a couple were recorded side-by-side and positioned on their host’s belly. We surmise that at least one of the couples was a reproductive pair, as the belly of the larger fish was noticeably swollen in the last sighting, and the bulge on its belly was bilateral and extended almost uniformly to the vent, a strong indication of fully mature gonads. Moreover, its size matched those of the mature females of this diskfish species. To our knowledge, this is the first time that attachment fidelity of the whalesucker to any cetacean host is documented in the wild. We hypothesize that attachment fidelity to the same individual host increases the whalesucker’s chance to mate, and suggest further that the highly social nature of the spinner dolphins facilitates encounters between potential mating partners. Our study indicates that host fidelity possibly is not an uncommon feature of the whalesucker behaviour, albeit difficult to recognise. In one of the above recorded whalesuckers the natural marking was a crescentic scar characteristic of the wounds inflicted by the cookiecutter Isistius brasiliensis (Dalatiidae), a first record of the attack of this shark to any diskfish species.